2017
DOI: 10.1007/s12310-017-9223-6
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Teachers’ Interpersonal Styles and Well-Being and Ill-Being in Secondary School Physical Education Students: The Role of Need Satisfaction and Need Frustration

Abstract: This study examined the associations among physical education students' perceptions of their teachers' autonomy-supportive and controlling interpersonal styles, need satisfaction and need frustration, and indices of psychological well-being (subjective vitality) and ill-being (negative affect). The results from 591 Chinese secondary school students in Hong Kong indicated that the relationship between students' perceptions of autonomy-supportive teaching behaviors and subjective vitality was primarily mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 63 publications
10
50
1
6
Order By: Relevance
“…We also considered specific cross-path relationships (i.e., the relationship between one variable belonging to the bright pathway and another variable belonging to the dark pathway). It was specifically hypothesized that a perceived task-oriented climate would be a buffer against need frustration (Hypothesis 2a), and also that a perceived ego-oriented climate would prevent experiences of need satisfaction (Hypothesis 2b Consistent with previous studies in the PE context (Haerens et al 2015;Liu et al 2017), we expected the theoretical symmetrical paths (e.g., between task-oriented climate and need satisfaction), to be more strongly significant than the hypothetical cross-paths (e.g., between task-oriented climate and need frustration) (Hypothesis 2c).…”
Section: The Present Studymentioning
confidence: 67%
See 1 more Smart Citation
“…We also considered specific cross-path relationships (i.e., the relationship between one variable belonging to the bright pathway and another variable belonging to the dark pathway). It was specifically hypothesized that a perceived task-oriented climate would be a buffer against need frustration (Hypothesis 2a), and also that a perceived ego-oriented climate would prevent experiences of need satisfaction (Hypothesis 2b Consistent with previous studies in the PE context (Haerens et al 2015;Liu et al 2017), we expected the theoretical symmetrical paths (e.g., between task-oriented climate and need satisfaction), to be more strongly significant than the hypothetical cross-paths (e.g., between task-oriented climate and need frustration) (Hypothesis 2c).…”
Section: The Present Studymentioning
confidence: 67%
“…Recent evidence in PE indicates that teachers can catalyze a 'bright' pathway toward more optimal functioning if they effectively nurture students' BPN for relatedness, competence, and autonomy (e.g., Haerens et al 2015;Sánchez-Oliva et al 2014), while they can also elicit a 'dark' pathway if their teaching strategies induce feelings of need frustration (e.g., Haerens et al 2015;Haerens et al 2018;Liu, Bartholomew, and Chung 2017). Moreover, need satisfaction and need frustration have been found to be associated with different antecedents (e.g., need-supportive or needthwarting teaching behavior) in PE lessons (Haerens et al 2015;Haerens et al 2018), suggesting that considering them as separate constructs is highly relevant.…”
Section: Basic Psychological Need Satisfaction and Need Frustrationmentioning
confidence: 99%
“…However, a recent study by González-Cutre, Romero-Elías, Jiménez-Loaisa, Beltrán-Carrillo, and Hagger [59] showed how support for autonomy was positively related to each of the factors of psychological needs, including novelty. Similarly, different studies in the field of PE (i.e., [60][61][62][63]) have shown how support for autonomy predicted the thwarting of psychological needs in a negative way; on the contrary, psychological control predicted them in a positive way, but the thwarting of psychological needs was analyzed in a global way and not through the factors that compose it. Thus, the results of the present study are in line with the results shown in previous studies and within the postulates of SDT.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the model proposed by Bostic et al [57], results of the CFA supported the hypothesized unidimensional structure of the SVS. The six-item model has been previously tested with a sample of Spanish adolescents [59], showing a good fit to the data, and this model has been widely used in different populations in Europe and China [88][89][90].…”
Section: Discussionmentioning
confidence: 99%